Discrete symmetries, invisible axion, and lepton number symmetry in an economic 3-3-1 model - Dias, Alex G.; Pires, C. A de S.; Rodrigues da Silva, P. S. [UNESP] (American Physical Society (APS), 2003)
We show that Peccei-Quinn and lepton number symmetries can be a natural outcome in a 3-3-1 model with right-handed neutrinos after imposing a [Formula Presented] symmetry. This symmetry is suitably accommodated in this model when we augment its spectrum by including merely one singlet scalar field. We work out the breaking of the Peccei-Quinn symmetry, yielding the axion, and study the phenomenological consequences. The main result of this work is that the solution to the strong CP problem can be implemented in a natural way, implying an invisible axion phenomenologically unconstrained, free of domain wall formation, and constituting a good candidate for the cold dark matter. © 2003 The American Physical Society.